Training to improve skill in managing and reporting regular BOS Fund in SMA/SMK - I. Irawan; Iskandar Muda; Ari Irawan (Universitas Muhammadiyah Malang, 2023)
Problems related to the management of BOS funds are that they are still not optimal in implementing procedures and reporting of BOS funds. Conditions like this often trigger errors in data input and financial reporting of BOS funds that are not in accordance with Permendikbud No 6 of 2021. The purpose of this service is to increase the accountability of BOS funds reporting at Senior High and Vocational. The object of this service is the Education Authorities of Lubuk Pakam Sumatera Utara. The approach to implementing this community service is to carry out financial observations and training conducted by the community service team. The results of this community service activity show that the understanding of BOS chamberlain at Senior High and Vocational has been implemented in managing BOS funds. Procedures and reporting of BOS funds must comply with the principle of Accountability which is the principle of public accountability. This means that the budgeting process starting from planning preparation and implementation must be truly reportable and accountable. The implementation of the BOS funds at SMK program has followed the guidelines prepared by the Government in the 2022 BOS at Senior High and Vocational Technical Guidelines by prioritizing the concept of School Based Management (SBM), namely the principles of self-management and participatory, transparent, accountable, democratic, effective and efficient, orderly administration and reporting, and mutual trust. In the SBM concept, schools are required to independently explore, allocate, demand priorities, control and be accountable for empowering resources, both to the community and the government.